YB-1 Is a Novel Target for the Inhibition of a-Adrenergic-Induced Hypertrophy - Heger, Jacqueline; Partsch, Stefan; Harjung, Claudia; Varga, Zoltán V.; Baranyai, Tamás; Weiß, Johannes; Kremer, Lea; Locquet, Fabian; Leszek, Przemyslaw; Ágg, Bence; Benczik, Bettina; Ferdinandy, Péter; et al. (My University, 2023)
Cardiac hypertrophy resulting from sympathetic nervous system activation triggers the development of heart failure. The transcription factor Y-box binding protein 1 (YB-1) can interact with transcription factors involved in cardiac hypertrophy and may thereby interfere with the hypertrophy growth process. Therefore, the question arises as to whether YB-1 influences cardiomyocyte hypertrophy and might thereby influence the development of heart failure. YB-1 expression is downregulated in human heart biopsies of patients with ischemic cardiomyopathy (n = 8), leading to heart failure. To study the impact of reduced YB-1 in cardiac cells, we performed small interfering RNA (siRNA) experiments in H9C2 cells as well as in adult cardiomyocytes (CMs) of rats. The specificity of YB-1 siRNA was analyzed by a miRNA-like off-target prediction assay identifying potential genes. Testing three high-scoring genes by transfecting cardiac cells with YB-1 siRNA did not result in downregulation of these genes in contrast to YB-1, whose downregulation increased hypertrophic growth. Hypertrophic growth was mediated by PI3K under PE stimulation, as well by downregulation with YB-1 siRNA. On the other hand, overexpression of YB-1 in CMs, caused by infection with an adenovirus encoding YB-1 (AdYB-1), prevented hypertrophic growth under α-adrenergic stimulation with phenylephrine (PE), but not under stimulation with growth differentiation factor 15 (GDF15; n = 10–16). An adenovirus encoding the green fluorescent protein (AdGFP) served as the control. YB-1 overexpression enhanced the mRNA expression of the Gq inhibitor regulator of G-protein signaling 2 (RGS2) under PE stimulation (n = 6), potentially explaining its inhibitory effect on PE-induced hypertrophic growth. This study shows that YB-1 protects cardiomyocytes against PE-induced hypertrophic growth. Like in human end-stage heart failure, YB-1 downregulation may cause the heart to lose its protection against hypertrophic stimuli and progress to heart failure. Therefore, the transcription factor YB-1 is a pivotal signaling molecule, providing perspectives for therapeutic approaches.
Keywords: ddc:610